Sterols from stems of Momordica cochinchinesis (Lour.) Spreng. - Mai, Nguyen Thi; Kiem, Phan Van; Thu, Vu Kim (Vietnam Journal of Chemistry, 2017)
Three known sterols, polypodine B (1), (22E,24R)-24-methylcholesta-2,22-diene-3β,5α,6β-triol (2) and chondrillasterol (3) were isolated from the stems of Momordica cochinchinesis (Lour.) Spreng. Their chemical structures were successfully determined using NMR and ESI-MS analysis as well as in comparison with the reported data. All compounds were reported from Momordica genus for the first time. Keywords. Momordica cochinchinesis, Cucurbitaceae, steroid.